VIETNAMESE EFL COLLEGE STUDENTS’ SENSITIVITY TO THE ENGLISH MASS-COUNT DISTINCTION - Quyen, Nguyen Thi (VNU Journal of Foreign Studies, 2022)
This paper examines how Vietnamese learners of L2 English interpret the English mass-count distinction. In a picture-based judgment experiment, sixty-two college students learning English as their L2 made judgments that reflect their sensitivity to the English mass-count distinction and morphosyntax-semantics mappings. The findings indicate that Vietnamese learners of L2 English correctly based their judgments on number for count nouns (e.g., cup ) and object-mass nouns (e.g., furniture ), and on volume for substance-mass nouns (e.g., milk ). In addition, Vietnamese learners performed at chance level with English flexible nouns, i.e., nouns that are interpreted as count in the presence of the plural marker - s and as mass in its absence. Furthermore, no significant correlation was found between learners’ L2 proficiency scores and their judgments. Taken together, these findings suggest that Vietnamese college students are insensitive to the morphosyntactic cues of English flexible nouns when interpreting their meaning. Such insensitivity might be due to L1 effects and can be independent of L2 proficiency.